Current Animal Models for Understanding the Pathology Caused by the Respiratory Syncytial Virus - Altamirano-Lagos, María José; Díaz, Fabián E.; Mansilla, Miguel Andrés; Rivera-Pérez, Daniela; Soto, Daniel; McGill, Jodi L.; Vasquez, Abel E.; Kalergis, Alexis M. (Frontiers in Microbiology, 2019)
The human respiratory syncytial virus (hRSV) is the main etiologic agent of severe lower respiratory tract infections that affects young children throughout the world, associated with significant morbidity and mortality, becoming a serious public health problem globally. Up to date, no licensed vaccines are available to prevent severe hRSV-induced disease and the generation of safe-effective vaccines have been a challenging task, requiring constant biomedical research aimed to overcome this ailment. Among the difficulties presented by the study of this pathogen, arises the fact that there is no single animal model that resembles all aspects of the human pathology, which is due to the specificity that this pathogen has for the human host. Thus, for the study of hRSV, different animal models might be employed, depending of the goal of the study. Of all the existing models, the murine model has been the most frequent model of choice for biomedical studies worldwide and has been of great importance at contributing to the development and understanding of vaccines and therapies against hRSV. However, several additional different models for studying hRSV, such as other rodents, mustelids, ruminants and non-human primates have been explored, offering advantages over the murine model. In this review, we discuss the various applications of animal models to the study of hRSV-induced disease, the advantages and disadvantages of each model, highlighting the potential of each model to elucidate different features of the pathology caused by the hRSV infection.